Antifungal properties of an actinomycin D‐producing strain, Streptomyces sp. IA1, isolated from a Saharan soil. (3rd October 2014) - Toumatia, Omrane; Yekkour, Amine; Goudjal, Yacine; Riba, Amar; Coppel, Yannick; Mathieu, Florence; Sabaou, Nasserdine; Zitouni, Abdelghani
<x xml:space="preserve">Abstract</x> An actinomycete strain named IA1, which produced an antimicrobial compound, was isolated from a Saharan soil in In Amenas, Algeria. The study of the 16S rDNA sequence of this strain permitted to relate it to Streptomyces mutabilis NBRC 12800T (99.93% of similarity). Strain IA1 exhibited strong activity against a wide range of plant pathogenic fungi. One bioactive compound produced in large amounts (46.7 mg L−1 day−1), named YA, was isolated and purified by TLC and reverse phase HPLC. The structure elucidation of the pure substance, using combined data from UV visible, NMR spectra, and mass spectrometry, permitted to identify it as actinomycin D, and was thus found for the first time in S. mutabilis related species. The biocontrol abilities of the strain IA1 and compound YA were evaluated through two diseases, i.e., chocolate spot of field bean and Fusarium wilt of flax. The occurrence of the two fungal diseases was effectively reduced. The reduction of chocolate spot disease symptoms reached 80 and 91.7% with IA1 and YA seedlings pretreatments, respectively. Soil pretreatment with IA1 or YA also allowed to reduce Fusarium wilt disease impact by almost 60%.